Is there a standardised consent process within the surgical specialties?. Issue 6 (December 2020) - Hall, James; Farrell, Ian; Kalipershad, Sujala; Hill, James
Abstract: Introduction: The consent process is central to surgical practice. Subsequent to landmark cases such as Montgomery and Thefaut there is increasing consensus that consent should be a staged process. The aim of our survey was to identify if there was any homogeneity in the practice of surgeons with regards to the consent process in comparison to national guidelines. Methods: Our survey was distributed to a broad range of surgical specialties via an anonymous Google Forms questionnaire available online. Consultant Surgeons and Specialist registrars across the United Kingdom were then contacted via their relevant surgical societies and professional. Data collection was based on the Montgomery principles: consent location; face to face meetings; information leaflets (including their source); distribution of copies of letters and consent forms; use of percentage risks; use of pre-printed consent forms. Results: The total number of replies was 325. The majority of consent was taken on the day of surgery (166/319; 50.8%). Scheduled meeting for the consent process occurred routinely in only 87 cases (87/319; 27.3%). 103 (103/319; 32.9%) responders indicated the use of pre-printed consent forms. Of which 93 (93/103; 90.3%) were produced locally. Risk percentages were routinely used by 103 responders (103/319; 32.9%) Nearly two-thirds never write specific risk percentages routinely (205/319; 64.3%). Copies of consent forms were routinely given out by 210 responders (210/319; 65.8%). Supporting information was routinely given to patients in 248 cases (248/319; 77.7%). Conclusion: Our survey documents significant variation in the practice of consent despite clear guidance on best practice. We believe that most surgeons welcome a more thorough and robust consent process, but hey need the time and infrastructure to be able to do it Introduction. Highlights: The total number of responders was 325. The majority of consent was taken on the day of surgery (50.8%). Scheduled meeting for consent process occurred routinely in only 87 cases (27.3%). Risk percentages were routinely used by 103 responders (32.9%). Significant variation in consenting despite clear guidance on best practice.